The Influence of Non-Economic Factors on GeneralTakaful Adoption Among MSMEs’ in NorthwestNigeria - Safeza Mohd Sapian; Norhazlina Ibrahim; Syadiyah Abdul Shukor; Nurudeen Abdulkadir (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA